Evaluation of hydrodynamic performance of pre-swirl and post-swirl ESDs for merchant ships by numerical towing tank procedure. (15th April 2019) - Sakamoto, Nobuaki; Kume, Kenichi; Kawanami, Yasutaka; Kamiirisa, Hikaru; Mokuo, Kenji; Tamashima, Masahiro
Abstract: Due to the EEDI regulation, recent merchant ships have strictly been required to achieve certain rate of energy saving, and thus equipment of energy saving devices (ESDs) has been quite popular. The purpose of this study is to investigate the working principle of pre and post swirl type ESDs via complementary use of experiment and viscous computational fluid dynamics (CFD). Three different hull forms (Japan Bulk Carrier: JBC, Duisburg Test Case container ship: DTC, and coastal tanker: COT) with three different ESDs are of the interest. Propeller open water, resistance and self propulsion tests are totally replaced by viscous CFD simulations, termed numerical towing tank procedure. For JBC, detailed investigations of self propulsion parameters, balance of kinetic energy flux, local flow and propeller loads clarify the working principle of its stern duct. For DTC, the present computations find out that vertical distribution of the twist angle of its rudder and the distance between propeller boss cap and the rudder bulb should be modified. For COT, the scale effect in axial and tangential components of its nominal and total wake are studied. In the meantime, the reason of deterioration/improvement in self propulsion coefficients by the pre swirl stator fins are identified.